2023
DOI: 10.5194/wes-8-661-2023
|View full text |Cite
|
Sign up to set email alerts
|

Nonlinear inviscid aerodynamics of a wind turbine rotor in surge, sway, and yaw motions using a free-wake panel method

Abstract: Abstract. We investigate the aerodynamics of a surging, heaving, and yawing wind turbine with numerical simulations based on a free-wake panel method. We focus on the UNAFLOW (UNsteady Aerodynamics of FLOating Wind turbines) case: a surging wind turbine which was modeled experimentally and with various numerical methods. Good agreement with experimental data is observed for amplitude and phase of the thrust with surge motion. We achieve numerical results of a wind turbine wake that accurately reproduce experim… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 28 publications
2
4
0
Order By: Relevance
“…b vel > 15%) of the surging NREL 5 MW rotor around the design operation condition, Wen et al found that the rise of the power amplitude becomes slightly nonlinear. A similar observation was found by Ribeiro et al (2023) for the thrust force, where a FVW panel method was used to simulate the UNAFLOW rotor. In addition, a rising phase shift between the surge velocity and rotor thrust was reported independent from b vel , which was also observed by Mancini et al (2020) earlier.…”
Section: Numerical Investigationssupporting
confidence: 80%
See 2 more Smart Citations
“…b vel > 15%) of the surging NREL 5 MW rotor around the design operation condition, Wen et al found that the rise of the power amplitude becomes slightly nonlinear. A similar observation was found by Ribeiro et al (2023) for the thrust force, where a FVW panel method was used to simulate the UNAFLOW rotor. In addition, a rising phase shift between the surge velocity and rotor thrust was reported independent from b vel , which was also observed by Mancini et al (2020) earlier.…”
Section: Numerical Investigationssupporting
confidence: 80%
“…A hint on such behaviour can also be found in Ribeiro et al (2023). Panel method simulations showed a lower-than-expected thrust amplitude at a rotor reduced frequency slightly below 5.…”
Section: Unaflow Rotormentioning
confidence: 63%
See 1 more Smart Citation
“…When assuming an inflow without shear and an axisymmetric wake, yaw can be considered equivalent to pitch; sway can be considered equivalent to heave, following a coordinate transformation. At small amplitude, the roll motion of FOWT can be approximated by the sway motion since the centre of gravity is far below the rotor hub centre (Ribeiro, Casalino & Ferreira 2023a). Here, we assume that the FOWT is forced to oscillate harmonically for each motion.…”
Section: Set-up Of Les Casesmentioning
confidence: 99%
“…Simulations that do not include flow separation, but include geometric nonlinear effects have been shown to capture the amplitude of the LCO associated with the first flutter mode of the Pazy wing (Riso and Cesnik, 2022), but not the subcritical effects. In the case of the present simulations, nonlinear geometry effects come from the structural model, while nonlinear inviscid aerodynamic effects (Ribeiro et al, 2023), come from the panel code. Flow separation is missing, meaning capturing the subcritical LCO is likely not possible, but achieving LCO for the first flutter mode should be.…”
Section: Limit Cycle Oscillationsmentioning
confidence: 99%